2011
DOI: 10.3109/14653249.2010.515582
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of allogeneic natural killer cell therapy to treat patients with recurrent ovarian and breast cancer

Abstract: Background Natural killer (NK) cells derived from patients with cancer exhibit diminished cytotoxicity compared with NK cells from healthy individuals. We evaluated the tumor response and in vivo expansion of allogeneic NK cells in recurrent ovarian and breast cancer. Methods Patients underwent a lymphodepleting preparative regimen: fludarabine 25 mg/m2 × 5 doses, cyclophosphamide 60 mg/kg × 2 doses, and, in seven patients, 200 cGy total body irradiation (TBI) to increase host immune suppression. An NK cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
317
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(326 citation statements)
references
References 52 publications
6
317
1
2
Order By: Relevance
“…Strategies to augment in vivo NK cell persistence and expansion might be required to reduce this chimeric effect; Treg reconstitution in the recipient, for example, can repress this chimerism. 179 Additionally, a phase II clinical trial using UCB-derived allogeneic NK cells has been performed in leukemia and myelodysplastic syndrome patients, but was terminated, and no conclusions can be drawn as to its efficacy.…”
Section: Clinical Trials Of Nk Cell-mediated Tumor Immunotherapymentioning
confidence: 99%
“…Strategies to augment in vivo NK cell persistence and expansion might be required to reduce this chimeric effect; Treg reconstitution in the recipient, for example, can repress this chimerism. 179 Additionally, a phase II clinical trial using UCB-derived allogeneic NK cells has been performed in leukemia and myelodysplastic syndrome patients, but was terminated, and no conclusions can be drawn as to its efficacy.…”
Section: Clinical Trials Of Nk Cell-mediated Tumor Immunotherapymentioning
confidence: 99%
“…Findings from the trial showed a lack of NK cell expansion and restricted anti-tumor effects in patients with ovarian and breast cancer. 37 This limited response may be due to the immunosuppressive effects of cancer cells on NK cells, as listed above. 28,38 Recently, research has also shown that some NK cells can become NK memory cells, which have a longer life span.…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…Although freshly isolated allogeneic NK cells have been utilized in clinical trials [14][15][16], cell numbers are …”
Section: Weimentioning
confidence: 99%